The Effect of Barefoot Morning Walking on Blood Pressure in Adults with Hypertension - Novitayanti, Eka; Proborini, Christiana Arin (Chakra Brahmanda Lentera Institute, 2026)
Background: Hypertension is a health problem that affects many people and carries the risk of serious complications if not properly treated. Walking barefoot in the morning is a non-pharmacological method believed to help lower blood pressure by stimulating nerve endings and increasing body relaxation. In low- and middle-income countries, walking barefoot is common. The public felt more productive rather than having to use. This study was conducted to analyze the effect of barefoot morning walking on blood pressure in hypertensive patients. Methods: This study used a one-group pre-experimental design with a one-group pretest-posttest approach. Technique collection sample, namely purposive, n 31, which meets the inclusion criteria, namely history of hypertension, willing given barefoot morning walk intervention according to established procedures, and criteria for respondents who cannot walk. Blood pressure was measured before and after the intervention using a validated digital blood pressure monitor. Data were analyzed using the Wilcoxon test. Results: The results of the study showed that before the intervention, most respondents were in the stage I hypertension category (64.5%), while after the intervention, the majority were in the prehypertension category (67.7%). Statistical tests showed a significant decrease in blood pressure in both systolic (p < 0.00 1 ) and diastolic (p < 0.00 1 ) blood pressure, thus indicating a significant effect of barefoot morning walking on reducing blood pressure. Conclusion: Barefoot morning walking intervention can reduce blood pressure in hypertensive patients, which can be applied to help control blood pressure.